2010
DOI: 10.1021/ie101210x
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Methylcyclohexane To Produce High-Purity Hydrogen Using Membrane Reactors with Amorphous Silica Membranes

Abstract: We developed a membrane reactor that can produce high-purity hydrogen in one step from methylcyclohexane. This membrane reactor combined a hydrogen-selective amorphous silica membrane prepared with dimethoxydiphenylsilane and oxygen and employing counter-diffusion chemical vapor deposition, and Pt/Al 2 O 3 catalyst. The silica membrane showed excellent hydrogen permeance at 573 K of the order of 10 -6 mol m -2 s -1 Pa -1 and high hydrogen/sulfur hexafluoride permselectivity of around 10 4 . The membrane reacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…The extent of the equilibrium shift was greater when a membrane with higher hydrogen permeance was used. Furthermore, it is noteworthy that we have successfully operated these membrane reactors Production Rate and Hydrogen Permeance through the DMDPS-derived Membrane during the Operation of the Membrane Reactor with no Carrier Gas or Sweep Gas 51) with no carrier gas or sweep gas, for the first time in the world. This means that high-purity hydrogen at atmospheric pressure can be obtained in a one-step procedure, and the produced hydrogen can then be directly supplied to a fuel cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of the equilibrium shift was greater when a membrane with higher hydrogen permeance was used. Furthermore, it is noteworthy that we have successfully operated these membrane reactors Production Rate and Hydrogen Permeance through the DMDPS-derived Membrane during the Operation of the Membrane Reactor with no Carrier Gas or Sweep Gas 51) with no carrier gas or sweep gas, for the first time in the world. This means that high-purity hydrogen at atmospheric pressure can be obtained in a one-step procedure, and the produced hydrogen can then be directly supplied to a fuel cell.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the permeances of H2, N2 and SF6 at 573, 473 and 373 K, respectively 51) . The permeance of H2 was around 10 Figs.…”
Section: Pore Size Control In the Preparation Of Silicamentioning
confidence: 99%
See 1 more Smart Citation
“…4c, nearly 100% of MCH are converted into hydrogen and toluene over the 0.45 wt% catalyst at 340 C. However, as the reaction temperature drops, the conversion of MCH decreases signicantly and reaches $50% at 280 C. The temperature-dependent conversion (Fig. [27][28][29] Meanwhile, it is very important for practical applications to obtain a high conversion at a high gas hourly space velocity (GHSV). 27 It was found that E a ¼ 47.1 kJ mol À1 for the in situ prepared Pt/CS, which is much lower than most of the catalysts synthesized by conventional methods.…”
Section: Catalystmentioning
confidence: 99%
“…From among these methods, organic chemical hydrides (hydrogenated aromatic compounds such as cyclohexane, methylcyclohexane, and decaline) have attracted researchers' attention because of their advantages, including (Itoh, Watanabe, Kawasoe, Sato, & Tsuji, 2008;Oda et al, 2010). Considering the fact that hydrogen has an explosive combustion rate and very high combustion temperature, special attention has been focused on establishing a low potential risk hydrogen storage and transportation system.…”
Section: An Overview On Cyclohexane Dehydrogenationmentioning
confidence: 99%